2018
DOI: 10.1016/j.ahj.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding GLP-1RA on mortality, cardiovascular events, and metabolic outcomes among insulin-treated patients with type 2 diabetes: A large retrospective UK cohort study

Abstract: Based on a large UK cohort in routine clinical practice, adding a GLP-1RA to insulin therapy is associated with a reduction in risk of composite CV events and all-cause mortality but a nonsignificant higher risk of hospitalization for heart failure in overweight patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 28 publications
2
36
0
1
Order By: Relevance
“…We identified sixteen observational cohort studies assessing CV outcomes, HHF and or all‐cause mortality in T2MD patients treated with GLP‐1 RAs: Best et al, 27 Mogensen et al, 28 Paul et al, 29 Vélez et al, 30 Patorno et al, 31 Kannan et al, 32 Ekström et al, 33 Anyanwagu et al, 34 Suissa et al, 35 Zimmerman et al, 36 Toulis et al, 37 Anyanwagu et al, 38 Patorno et al, 39 Dawwas et al, 40 Svanström et al 41 and O'Brien et al 42 The total number of patients exposed to GLP‐1 RAs was 285,436; ranging from 219 33 to 160,803 40 . (Table 2) Study periods span from 2005 27 to 2015 37 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified sixteen observational cohort studies assessing CV outcomes, HHF and or all‐cause mortality in T2MD patients treated with GLP‐1 RAs: Best et al, 27 Mogensen et al, 28 Paul et al, 29 Vélez et al, 30 Patorno et al, 31 Kannan et al, 32 Ekström et al, 33 Anyanwagu et al, 34 Suissa et al, 35 Zimmerman et al, 36 Toulis et al, 37 Anyanwagu et al, 38 Patorno et al, 39 Dawwas et al, 40 Svanström et al 41 and O'Brien et al 42 The total number of patients exposed to GLP‐1 RAs was 285,436; ranging from 219 33 to 160,803 40 . (Table 2) Study periods span from 2005 27 to 2015 37 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…THIN database has been validated and shown it to be demographically representative of the UK population in terms of demography, disease prevalence and mortality [21]. We have published extensively in our research group, using the THIN database in evaluating diabetesrelated outcomes in routine clinical practice [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…While the mechanism for the reduction of mortality outcome remains unclear, concurrent use of a glucose-lowering therapy with insulin is used widely. In a previous study within this same population cohort, we showed that the use of GLP-1 with insulin was associated with reduced CV events and total mortality compared with insulin alone [23]. Thus, the identification of patients at a high risk of CV events based on ACR and eGFR status would not only trigger the application of an aggressive CV reduction strategy, but also a concurrent use of appropriate glucose-lowering therapies with favourable effects on weight, albuminuria, and CV outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been validated and shown to be demographically representative of the UK population in terms of disease demography, prevalence, and mortality [21]. Like many others, our research group has extensively used it in evaluating diabetes-related outcomes in routine clinical practice [22, 23]. …”
Section: Methodsmentioning
confidence: 99%